Knowledge management and organizational performance in the service industry: The role of transformational leadership beyond the effects of transactional leadership - Birasnav, M. (Journal of Business Research, 2014)
This study examines a comprehensive model comprising of various relationships between transformational and transactional leadership, knowledge management (KM) process, and organizational performance. Data are collected from human resource managers and general managers working in 119 service firms. Exploratory factor analysis and hierarchical regression analysis are used to analyze the proposed hypotheses. The results indicate that transformational leadership has strong and positive effects on KM process and organizational performance after controlling for the effects of transactional leadership. Further, KM process partially mediates the relationship between transformational leadership and organizational performance after controlling for the effects of transactional leadership. Implications and directions for future research are also discussed.
Keywords: Knowledge management; Organizational performance; Transactional leadership; Transformational leadership; dept.mgt

Supply chain integration, advanced manufacturing technology, and strategic leadership: An empirical study - Birasnav, M.; Bienstock, Joshua (Computers & Industrial Engineering, 2019)
Top management support is a crucial investment at any manufacturing firm striving to integrate supply chain partners with the manufacturing processes so as to achieve a competitive advantage. Though the effectiveness of different leadership behaviors exhibited in top-level management has been documented in the leadership literature, the influence of such behaviors on developing linkages with supply chain partners has not been extensively examined. In order to bridge this research gap, this study examines the interlinkages between strategic leadership theory and supply chain integration theory. In addition, it also investigates the interrelationships between these two theories in the context of implementation of advanced manufacturing technology. Data has been collected from 107 small manufacturing companies and was analyzed using structural equation modelling. Results show that transactional leadership exhibited in top-level management is positively related to internal integration within the manufacturing companies. Transformational leadership behavior exhibited in top-level management and advanced manufacturing technology implemented in the shop floor of these companies are positively related to the integration of external supply chain partners. In addition, we also found that in those instances where small manufacturing companies place a high emphasis on the implementation of advanced manufacturing technology, they are guided by transformational leaders who strongly integrate their companies with customers.
Keywords: Advanced manufacturing technology; Customer integration; Internal integration; Small manufacturing industries; Strategic leadership; Supplier integration; dept.mgt; peer-reviewed

Integrating Theories of Strategic Leadership, Social Exchange, and Structural Capital in the Context of Buyer–Supplier Relationship: An Empirical Study - Birasnav, M.; Mittal, Rakesh; Dalpati, Avadhesh (Global Journal of Flexible Systems Management, 2019)
This study is aimed at improving the purchasing cycle time in a buyer–supplier relationship by integrating the facets of strategic leadership, social exchange, and social capital theories. We developed and tested a conceptual model that postulated relationships among strategic leadership behavior, relational trust and commitment, structural capital, and purchasing cycle time. Data were collected from purchase managers and their employees working in 105 manufacturing companies and analyzed using structural equation modeling technique. Our findings indicated that strategic leadership behaviors are positively related to trust in the buyer–supplier relationship. In addition, trust enhances relational commitment between buyer and supplier, which in turn positively relates to information sharing and supplier development. Further, increased information sharing in the relationship results in reduced purchasing cycle time. Implications for both theory and practice are discussed in depth, and directions for future research are suggested.
Keywords: Cycle time; Information sharing; Relational commitment; Relational trust-Strategic leadership; Supplier development; dept.mgt; peer-reviewed

Integration of Social Capital and Organizational Learning Theories to Improve Operational Performance - Birasnav, M.; Chaudhary, Richa; Scillitoe, Joanne (Global Journal of Flexible Systems Management, 2019)
This study focuses on integrating the premises of social capital theory and the theory of organizational learning to improve the operational performance of firms nurturing the buyer–supplier relationship. Social capital theory highlights the importance of developing social relationships between firms to create valuable resources and collectively access critical resources. Organizational learning theory highlights that the learning capacity of an organization strongly depends on top-level leaders’ behaviors, organizational structure, culture, and flexibility, and uncertainties in the environment in which the organization functions. Though many studies have focused on the impact of social capital on performance improvements in the buyer–supplier relationship, the interlinkages between social capital and organizational learning have not been given much attention. Based upon these theories, a system-focused perspective, which showcases the antecedents and outcome of the relationship between collaborative communication and learning, has been proposed in this study. A literature review has been carried out to support the linkages in the proposed conceptual model. Findings suggest that transformational buyers support creating cognitive capital with suppliers. This cognitive capital influences the structural capital, which supports improving the understanding of each party’s processes in the buyer–supplier relationship when parties have high long-term orientation. Improved learning capability reshapes organizations into flexible systems capable of responding quickly to customer requirements, and consequently, they realize a higher performance level.
Keywords: Collaborative communication; Information technology competency; Long-term orientation; Organizational learning; Supplier knowledge; Transformational leadership; dept.mgt

Linking Leadership Behaviors and Information Exchange to Improve Supply Chain Performance: A Conceptual Model - Birasnav, M.; Mittal, Rakesh; Loughlin, Selene (Global Journal of Flexible Systems Management, 2015)
Organizations striving to improve cycle time concentrate on developing long-term relationship with suppliers. In order to support organizational efforts, this study develops a conceptual model that explores the relationships among leadership behaviors, relational commitment and trust, information exchange, and cycle time. Although the supply chain management literature mentions leadership behavior in the context of supply chain, there are no studies that examine the impact of leadership behaviors on cycle time. This study proposes that transformational and transactional leadership behaviors of buyers increase the flow of information to suppliers directly as well as indirectly through relational commitment and trust, and these relationships also influence cycle time. However, it also proposes that the impact of transformational leadership behaviors on relational commitment and trust and information exchange is stronger than the impact of transactional leadership behaviors. Additionally, both uncertain environment and supplier base have potential to play moderation roles in the relationship between transformational leadership and relational commitment and trust and between transformational leadership and information exchange.
Keywords: Cycle time; Information exchange; Relational commitment; Relational trust; Supplier base; Transactional leadership; Transformational leadership; dept.mgt; peer-reviewed